(untitled) (Revista de Crítica Literaria Latinoamericana, 2015)
"The novel Simone (2013) by the Puerto Rican Eduardo Lalo constitutes a “lettered epic” in which the intellectual is seen as a figure of resistance against the neoliberal economy and consumist society. From the defense of the absolute values of writing and art, the intellectual is configured as a “heroic loser” that remains outside of society because he refuses any kind of negotiation with the dominant order. Its hierarchical view and isolation from the crowd allows us to include this novel in the modernist (Rodó, Dario) and Puerto Rican traditions (Pedreira and Marqués) in which anti-imperialism has not necessarily meant a democratic or anti-classist position."